Determination of Secondary Metabolite Levels in Ethanol Extract of Clove leaves (Syzygium aromaticum L.) Using LC-HRMS Methods - Tuldjanah, Muthmainah; Sasdila, Sasdila; Yanuarty, Rezky; Wulandari, Ayu; Tandi, Joni (Jurnal Biologi Tropis, 2024)
The use of plants as raw materials for medicinal purposes has become increasingly prevalent due to the diverse secondary metabolites they can produce. Clove leaves (Syzigium aromaticum L.) are known for their antimicrobial, antioxidant, anti-inflammatory, analgesic, anticancer, anesthetic, aphrodisiac, and antipyretic properties. This study aims to determine the levels of secondary metabolites in clove leaves using the LC-HRMS method. The results showed that the ethanol extract of clove leaves contained 34 compounds, with the compounds (-)-Caryophyllene oxide and Miquelianin having the highest chromatogram peaks at 9.714195% and 8.712299% of the compound composition, respectively.